Factors Affecting Students’ Confidence in Public Speaking - Pratama, Muhammad Arif (JOLLT Journal of Languages and Language Teaching, 2018)
The researcher aimed to find out an internal and external factors that affected students’ confidence in public speaking performance. The kind of this research was qualitative, this study is dealing with Miles and Huberman theory, the sample of this research was consist 5 members, the technique of collecting data used recording, note taking and questionnaires which was consit of 5 items and each item consisted of four options (very agree, agree, disagree, very disagree). The technique of data analysis used reduction, display, veryfiying the data for recording and note taking, meanwhile for questionnaires the researcher was used tabulation, computation and clarifiying the internal and external factors that affect students’ confidence in public speaking performance.